Rozpoznawalność marek wybranych produktów (wyniki badań ankietowych) - Witkowska, Dorota; Witkowski, Janusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2007)
In the paper we present the results of the inquiry concerning 67 selected brands of products. The respondents were asked to evaluate the recognition and the frequency of purchasing products belonging to the analyzed brands, as well as the market position of selected brands and the quality of products. The analysis of questionnaires is provided applying relative frequency measures and correlation analysis